Evaluation of right ventricular function in fetal hypoplastic left heart syndrome by color tissue Doppler imaging. (June 2016) - Graupner, O.; Enzensberger, C.; Wieg, L.; Willruth, A.; Steinhard, J.; Gembruch, U.; Doelle, A.; Bahlmann, F.; Kawecki, A.; Degenhardt, J.; Wolter, A.; Herrmann, J.; et al.
ABSTRACT: Objective: Postnatal outcome of fetuses with hypoplastic left heart syndrome (HLHS) is determined mainly by right ventricular function. Our study examines whether there are differences in right ventricular function during gestation of fetuses with HLHS compared with healthy fetuses. Methods: A prospective study was conducted including 20 fetuses with HLHS and 20 gestational age‐matched controls. Peak systolic and diastolic right ventricular free wall velocities were assessed using color tissue Doppler imaging (c‐TDI). Subsequently, isovolumic time intervals, ejection time (ET′), E′/A′ ratio and tissue Doppler‐derived myocardial performance index (MPI′) were calculated. Possible changes to c‐TDI indices during the course of pregnancy in both the HLHS group and the control group were investigated. Results: Examination of right ventricular function revealed significantly lower E′ velocities (13.6 vs 21.0 cm/s; P = 0.017) and E′/A′ ratios (0.55 vs 0.76; P = 0.012) and prolonged isovolumic contraction time (ICT′) (57.0 vs 45.7 ms; P = 0.008) in the HLHS group compared with healthy fetuses. Furthermore, isovolumic relaxation time and MPI′ increased significantly with gestational age in HLHS fetuses but not in controls. Values for systolic and diastolic peak velocities (E′, A′, S′), ET′ and ICT′ did not change significantly during gestation in either group. Conclusion: Right ventricular function in HLHS is altered as early as in fetal life, well before palliative surgery is performed. Future research should provide further insight into ventricular remodeling during gestation in cases of HLHS. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.